2019
DOI: 10.1158/0008-5472.can-18-3521
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel RAS Signaling Therapeutic Vulnerabilities in Diffuse Intrinsic Pontine Gliomas

Abstract: Diffuse intrinsic pontine gliomas (DIPG) are incurable brain tumors with an aggressive onset. Apart from irradiation, there are currently no effective therapies available for patients with DIPG, who have a median survival time of less than one year. Most DIPG cells harbor mutations in genes encoding histone H3 (H3K27M) proteins, resulting in a global reduction of H3K27 trimethylation and activation of oncogenic signaling pathways. Here we show that the H3K27M mutations contribute to RAS pathway signaling, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…We found that, both in vitro and in vivo, these pathways were epigenetically activated in an H3.3K27M-dependent fashion, including through upregulation of PDGFRA and MYC. This is supported by recent work showing that H3.3K27M leads to in vitro activation of the RAS/MAPK cascade 66 and the finding that a MYC superenhancer was among the most highly activated by the presence of H3K27M 67 . Together, this suggests that H3.3K27M-mediated epigenetic changes activate RAS/ MAPK and MYC, with H3.3K27M epigenetically activating multiple members of the RAS/MAPK cascade as well as its downstream transcriptional targets.…”
Section: Discussionsupporting
confidence: 65%
“…We found that, both in vitro and in vivo, these pathways were epigenetically activated in an H3.3K27M-dependent fashion, including through upregulation of PDGFRA and MYC. This is supported by recent work showing that H3.3K27M leads to in vitro activation of the RAS/MAPK cascade 66 and the finding that a MYC superenhancer was among the most highly activated by the presence of H3K27M 67 . Together, this suggests that H3.3K27M-mediated epigenetic changes activate RAS/ MAPK and MYC, with H3.3K27M epigenetically activating multiple members of the RAS/MAPK cascade as well as its downstream transcriptional targets.…”
Section: Discussionsupporting
confidence: 65%
“…A recent study transfected the H3K27M mutation into neural stem cells (NSCs) resulting in the activation of Ras and as upregulation of RNA and proteins of RTKs platelet derived growth factor (PDGFR) and EGFR, their respective growth factors, PDGFAA and EGF and initiated increased downstream signaling of the MEKK2‐MEK5‐ERK5 signaling cascade. Targeting of ERK5 inhibited tumor growth and promoted apoptosis [119] …”
Section: Epigeneticsmentioning
confidence: 99%
“… 59 Other groups have taken focused RNAi screening approaches to identify novel targets for DMG growth, including using a kinome-wide shRNA screen in DMG stem cell cultures, 60 an epigenomic/chromatin-associated shRNA screen in patient-derived DMG cultured cells, 61 and a RAS signaling pathway-targeted siRNA screen in both DMG stem cell and patient-derived cultures. 62 The latter two studies validated their findings in vivo using orthotopic xenograft models. 61 , 62 This technology, however, has been limited to assessing the molecular targets intrinsic to tumor cells and does not account for the diverse and complex extrinsic interactions of cancer cells with the tumor microenvironment.…”
Section: Genetic Screeningmentioning
confidence: 59%
“… 62 The latter two studies validated their findings in vivo using orthotopic xenograft models. 61 , 62 This technology, however, has been limited to assessing the molecular targets intrinsic to tumor cells and does not account for the diverse and complex extrinsic interactions of cancer cells with the tumor microenvironment. Additionally, there are technical challenges to RNAi screens, including the transfection process, resulting in incomplete penetrance and potentially only partial knockdown.…”
Section: Genetic Screeningmentioning
confidence: 59%